Comparisons among four types of absorbable plates used for internal fixation of zygomaticomaxillary complex fractures. Issue 3 (March 2019) - Chu, Seung Gyun; Lee, Joon Seok; Lee, Jeong Woo; Yang, Jung Dug; Chung, Ho Yun; Cho, Byung Chae; Choi, Kang Young
Abstract: Importance: Conventional plating systems include titanium plates for the fixation of facial bone fractures. However, titanium plates result in artifacts on computed tomography images and appear unstable on magnetic resonance images. Therefore, absorbable plates have been widely used for the fixation of facial bone fractures of late in Asia. Objective: To compare stability and symmetry among four different absorbable plates used for internal fixation of zygomaticomaxillary complex fractures. Participants: The subjects were patients with zygomaticomaxillary complex fractures that were diagnosed and treated by internal fixation with absorbable plates between January 2012 and April 2018. Patients aged ≤14 years and ≥76 years were excluded. Patients with other fracture types were also excluded. All patients underwent surgery within 2 weeks of the injury. Intervention: Internal fixation was performed with one of four types of absorbable plates, namely Inion ®, Polymax ®, Osteotrans ®, and Biosorb ® . Main outcome measures: The stability of the four plates was investigated by evaluation of the orbital height ratio (A'/A), zygoma angle (a'/a), distance (b'/b) from the midline, and gap (c) of the temporal process on three-dimensional facial computed tomography images obtained before, 3 weeks after, and 3–6 months after surgery. Any plate-associated complications were recorded. Results: In total, 400 patients were enrolled, and there were 100 patients in each of the four groups. There were no significant differences with regard to postoperative stability and relapse among the four plates. Moreover, facial symmetry showed no changes over time in any group. Complications such as infection and sensory disturbance were not frequent. All plates except Biosorb ® were palpable for more than 6 months after surgery, with Osteotrans ® remaining palpable for several years. Conclusions and relevance: Our findings suggest that all four types of absorbable plates are useful for treating isolated zygomaticomaxillary complex fractures. While Biosorb ® is unsuitable for severe comminuted fractures. Polymax ® and Inion ® are not bendable at room temperature. It is important to select an appropriate absorbable plate according to each patient's condition and the fracture severity.